GLOBAL CARLEMAN ESTIMATES FOR DEGENERATE PARABOLIC OPERATORS WITH APPLICATIONS - Cannarsa, P.; Martinez, P.; Vancostenoble, J. (Memoirs of the American Mathematical Society, 2016)
Degenerate parabolic operators have received increasing attention in recent years because they are associated with both important theoretical analysis, such as stochastic diffusion processes, and interesting applications to engineering, physics, biology, and economics. This manuscript has been conceived to introduce the reader to global Carleman estimates for a class of parabolic operators which may degenerate at the boundary of the space domain, in the normal direction to the boundary. Such a kind of degeneracy is relevant to study the invariance of a domain with respect to a given stochastic diffusion flow, and appears naturally in climatology models. Global Carleman estimates are a priori estimates in weighted Sobolev norms for solutions of linear partial differential equations subject to boundary conditions. Such estimates proved to be extremely useful for several kinds of uniformly parabolic equations and systems. This is the first work where such estimates are derived for degenerate parabolic operators in dimension higher than one. Applications to null controllability with locally distributed controls and inverse source problems are also developed in full detail. Compared to nondegenerate parabolic problems, the current context requires major technical adaptations and a frequent use of Hardy type inequalities. On the other hand, the treatment is essentially self-contained, and only calls upon standard results in Lebesgue measure theory, functional analysis and ordinary differential equations.